FACTORS AFFECTING THE HIGH EVENT OF LUNG TB IN NAGAN RAYA DISTRICT - Cut Sinta Simahbengi; Safrizal Safrizal (RADJA PUBLIKA, 2022)
Tuberculosis is an infectious disease caused by the bacterium Mycobacterium tuberculosis and is one of the top 10 causes of death worldwide. Indonesia is ranked second with the highest tuberculosis sufferers in the world after India. The survey results in August 2022 recorded 524 TB cases in Nagan Raya Regency, namely 331 men and 193 women. The purpose of this study was to analyze the relationship between the level of residential density, household contacts, and nutritional status on the incidence of pulmonary TB in Nagan Raya Regency. The type of research used is an analytic survey with a cross sectional design. Primary data obtained from the results of measurements and interviews using a questionnaire. The population in this study were 524 people with TB, the sample in this study amounted to 30 people with stratified random sampling. Analysis of research data is univariate and bivariate using Chi-Square test. The results showed that there was a relationship between residential density (Pvalue = 0.03 < 0.05), household contacts (Pvalue = 0.03 < 0.05), and nutritional status (P-value = 0.01 <0.05) with incidence of pulmonary TB.